Socioeconomic impacts and government assistance in the aftermath of landslides in Mayoon since 2010: A qualitative study on the vulnerable village of Hunza, Pakistan - Alam, Sunana; Afzal, Muhammad (Journal of Social Sciences and Management Studies, 2024)
The primary objective of this study is to assess the socioeconomic conditions of the inhabitants of village and evaluate the level of government support provided to them following the landslide. Additionally, the study aims to explore any changes in gender roles that occurred during the resettlement process. Mayoon is a modest village situated in Lower Hunza that has endured multiple landslides, rendering it susceptible to such natural like avalanches, landslides, Glacial Lake Outburst Floods (GLOFs), rock fall and flash floods. However, the frequency of landslides has increased since 2010, between 1994 and 2014, there were 78 floods, 16 landslides, and 8 debris flows. Ten participants i.e., five males and five females were purposively selected for this research. A semi-structured interview protocol was prepared keeping in view literature and personal observations, which consisted of 12 open-ended questions. Thematic analysis was used to analyze data. Four major themes were extracted from transcribed data namely, post disaster impact on living, resettlement issues, government role and gender role and disaster. It was discovered that most residents of Mayoon village, who were mainly farmers relying on agriculture, suffered from the landslides. The disaster not only destroyed the farmlands but also the cultural such as cultural sites once they gathered for religious activities. Once they gathered to perform their religious activities, the region was devastated by the disaster. Marriages, cultural events, and festivals were celebrated with zeal and zest, but post-disaster celebrations changed the way they were celebrated earlier. Many affected people had to move to different areas for safety, resulting in the loss of social connections among them. Despite knowing the risk of more landslides, most of them resettled in the same village due to unavailability of sufficient land. The local government failed to relocate them to a safer place and is unable to provide services to the affected individuals.